2008
DOI: 10.1097/ijg.0b013e318168f03e
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Catch Trial Methods Used in Standard Automated Perimetry in Glaucoma Patients

Abstract: The RTW method seems to underestimate FP response rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…In addition, there is a previous report which suggested the FPs with the SITA algorithm are underestimated compared with those in the Full-Threshold test, which uses the classic catch trials. 21 Also, as shown in Table 4, the mean rates of FL, FP, FN were low compared with GT indices. This may have contributed to the small effect of traditional indices and the selection of GT indices in the best models.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, there is a previous report which suggested the FPs with the SITA algorithm are underestimated compared with those in the Full-Threshold test, which uses the classic catch trials. 21 Also, as shown in Table 4, the mean rates of FL, FP, FN were low compared with GT indices. This may have contributed to the small effect of traditional indices and the selection of GT indices in the best models.…”
Section: Discussionmentioning
confidence: 90%
“…Similar studies that used either the HFA with the 30-2 pattern 16 or the Octopus perimeter 17 had results that were similar but not identical to ours. Thresholding algorithms may also alter results given that prior work showed significantly fewer FNs 21 and FPs 22 in tests incorporating SITA as compared to tests utilizing a full threshold algorithm. This suggests that although our results may be generalizable to different machines and testing algorithms, further research must be done to determine the true quantitative impact of VF metrics in different test scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The generalizability of our study to different perimeters and testing algorithms other than the SITA standard strategy and 24-2 pattern may also be limited; prior studies have shown, for instance, that there are overall significantly fewer FNs and FPs in tests incorporating SITA compared with a full threshold algorithm. 13,14 Our analyses also did not include some factors that have been shown to predict the reliability of VFs, including technician comments, patient experience with VF testing, or gaze tracking. 15,16 Last, our study did not use serial repeated measures of VFs to assess reliability; Bengtsson's approach of repeated measures (having patients repeat VF within 1 week) to measure reliability is certainly a viable alternative methodology, although it is impractical to apply to this methodology to a large sample of clinical patients.…”
Section: Discussionmentioning
confidence: 99%